Diabetes Mellitus and Increased Tuberculosis Susceptibility: The Role of Short-Chain Fatty Acids - Ekta Lachmandas; Corina N. A. M. van den Heuvel; Michelle S. M. A. Damen; Maartje C. P. Cleophas; Mihai G. Netea; Reinout van Crevel (Journal of Diabetes Research)
Type 2 diabetes mellitus confers a threefold increased risk for tuberculosis, but the underlying immunological mechanisms are still largely unknown. Possible mediators of this increased susceptibility are short-chain fatty acids, levels of which have been shown to be altered in individuals with diabetes. We examined the influence of physiological concentrations of butyrate on cytokine responses to Mycobacterium tuberculosis (Mtb) in human peripheral blood mononuclear cells (PBMCs). Butyrate decreased Mtb-induced proinflammatory cytokine responses, while it increased production of IL-10. This anti-inflammatory effect was independent of butyrate’s well-characterised inhibition of HDAC activity and was not accompanied by changes in Toll-like receptor signalling pathways, the eicosanoid pathway, or cellular metabolism. In contrast blocking IL-10 activity reversed the effects of butyrate on Mtb-induced inflammation. Alteration of the gut microbiota, thereby increasing butyrate concentrations, can reduce insulin resistance and obesity, but further studies are needed to determine how this affects susceptibility to tuberculosis.